Relationship between postpartum ovarian cyclicity profiles and some nutritional parameters in imported dairy cows in Algeria - Haffaf, Samia; Zemmouri, Laatra; Besbaci, Mohamed; Boukhechem, Said; Lafri , Mohamed (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
The objective of this study was to evaluate association among certain serum nutritional parameters, body condition score, and body weight, with resumption of ovarian cyclicity postpartum in Prim‘Holstein and Montbeliard dairy cows in Algeria. Milk samples were collected from 30 dairy cows twice weekly between days (d) 15 and 60 postpartum and progesterone concentration were determined in whole milk by ELISA. Body condition score and weight were determined at d 0, 30 and 60 postpartum, and blood samples were collected on d 0, 15, 30, 45 and 60 postpartum to determine serum concentration of urea, total proteins, cholesterol, triglycerides, glucose, calcium, phosphorus, aspartate transaminase and alanine transaminase. A cow was considered to have a normal ovarian cyclicity if ovulation occurs before the 35th d postpartum followed by a regular cycle. Results showed that only 40% of cows had normal resumption of ovarian cyclicity. Among abnormal resumption group, delayed first ovulation was the most recorded. Body condition score, body weight, and concentrations of cholesterol, urea and aspartate transaminase change significantly during the 60 d postpartum. Body condition score changed significantly during the first 60 d postpartum (P<0.0001). There was an effect of body condition score between the two groups normal resumption and abnormal resumption (P=0.02). There was an effect of body condition score and body condition score loss on abnormal resumption and normal resumption groups in all sampling time (P=0.01). There was an effect of body condition score loss ≥ 0.75, and loss < 0.75 on resumption of cyclicity in the first 30 d postpartum. Concentrations of urea and phosphorus were higher in cows with normal resumption than abnormal resumption. Monitoring body condition score is essential to control nutritional management, in order to minimize abnormal resumption of ovarian cyclicity in dairy cows.